Place Attachment - Altman, Irwin (Human Behavior and Environment, Advances in Theory and Research, 2012)
In step with the growing interest in place attachment, this volume examines the phenomena from the perspective of several disciplines-including anthropology, folklore, and psychology-and points towards promising directions of future research.